Detection and Quantification of Emerging Organic Pollutants in the Umgeni and Msunduzi Rivers - Moodley, Brenda; Birungi, Grace; Ndungu, Patrick (Water Research Commission, 2016)
BACKGROUND Globally, there is a strong interest and extensive research activities on emerging organic contaminants and there is an increasing need to monitor these compounds in order to understand the risks posed to human health and the environment at large. Emerging organic contaminants consist of a wide range of organic chemicals that are typically produced as a result of various anthropogenic activities. For this study, case studies were conducted on two of Durban’s key rivers; the Umgeni River and its main tributary, the Msunduzi River. Like many other rivers in South Africa, these 2 rivers are also under threat from pollution. These very same rivers also serve as one of the main sources for water supply for the surrounding population. Thus, this study is an attempt to study and monitor to some extent the levels, as well as the seasonal and spatial variation of selected organic pollutants in these rivers as they continue along their courses. AIMS The following were the aims of the project: Understand and determine the state of the art concerning selected emerging organic pollutants in Pietermaritzburg/Durban and KwaZulu-Natal’s water systems, to determine levels of emerging organic pollutants in selected water bodies and changes in their Concentrations from source to domestic outflow. Development and validation of protocols for the quantification of emerging organic pollutants in Natural and wastewater samples METHODOLOGY This study involved developing and optimizing methods for the determination of the levels of selected Polychlorinated biphenyl (PCB) congeners, organochlorine pesticides (OCPs), and pharmaceuticals and Personal care products (PPCPs) in the samples collected along the Umgeni and Msunduzi Rivers. Using Grab sampling, water and sediment samples were collected from several points along the Umgeni and Msunduzi Rivers. Samples were collected in amber glass bottles, and depending on the analyze of interest, some samples were preserved by adding sulfuric acid at the sample site. All samples were stored on ice and transported to the lab, and then stored in a 4°C fridge prior to extraction. Extractions were done using Solid phase extraction or liquid-liquid extraction with the water samples, and liquid extraction using an Ultrasound bath or sox let extraction with the sediment samples. Spiked samples were used to troubleshoot Method development and ascertain the suitability of the method when used on environmental samples. SUMMARY OF FINDINGS The presence of selected OCPs such as HCB, HCH (lindane), aldrin, heptachlor, diel Drin, endrin, mirex and DDT with its metabolites o,p-DDE, p,p-DDE, o,p-DDD, p,p-DDD, o,p-DDT and p,p-DDT and 8 PCB congeners, PCB 28, PCB 52, PCB 77, PCB 101, PCB 105, PCB 138, PCB 153 and PCB 180 in the Umgeni and Msunduzi Rivers were investigated. Concentrations for all selected OCPs and PCBs were determined, with excellent precision and accuracy, in all the samples collected. Generally, the Msunduzi River had higher levels of total OCPs and PCBs than the Umgeni River. In general, the total average PCB level in both the Umgeni and Msunduzi River sediments were very much lower than the interim fresh water sediment quality guidelines (ISQG) and probable effect level (PEL) permitted by the Canadian quality sediment guidelines. However, the levels were higher than the lowest effect level and far less than the severe effect level (SEL) as stipulated in the guidelines. OCPs on the other hand were generally higher than the ISQG values permitted in both the Umgeni and Msunduzi Rivers and is a cause for concern. With regards to pharmaceutical compounds, the presence of 18 pharmaceuticals representing five therapeutic classes, i.e. antibiotics, antipyretics, antiepileptic, stimulants and antipsychotic drugs, along the various sampling points on the Msunduzi and Umgeni Rivers were studied. Some of the pharmaceuticals were detected in both rivers. Wastewater samples were also analyzed and found to contain the selected pharmaceutical compounds. One other major outcome of this study was the development of a new method for analyzing pharmaceuticals found in the environment using GC-MS with derivatization, which is not the conventional method for analyzing pharmaceuticals. The method was optimized and validated and the results show the presence of the selected pharmaceuticals in the range of 0.0243-8.14 ng/mL with the Umgeni Estuary being the most contaminated site. A method was also developed for the analysis of polycyclic musk’s, a group of personal care products, and was used to quantify selected musk’s using simulated matrices as well as in the environment. The preliminary results show significant levels of the selected musk’s in both the Umgeni and Msunduzi Rivers. CONCLUSIONS Overall, this study provides a good understanding of the levels of selected pollutants such as PCBs, Pesticides, PPCPs and polycyclic musk’s in two major rivers in KwaZulu-Natal along their natural courses. This study presents data on the concentration levels from the source to the mouth and the joining point of the two rivers in different matrices such as surface water, pore water, sediment, bank soil and wastewater. Appropriate methods have been developed and have shown their applicability for the analysis of the selected pollutants in the environment of KwaZulu-Natal. This work has resulted in protocols that can be used to determine selected PCBs, OCPs, pharmaceuticals and polycyclic musk’s in environmental samples. The PCB levels were much higher within the Msunduzi River than the Umgeni River, which may be due to various activities along the rivers. PCBs were within acceptable limits though has the potential to become harmful due to prolonged exposure. OCPs were higher than the acceptable limits in many sites along both Rivers. Selected pharmaceutical compounds were detected and quantified in both river systems using LC-MS as well as a newly developed GC-MS method. Pharmaceuticals in some wastewater treatment plants in the KwaZulu-Natal region were also determined and were found to be mostly higher than in surface waters as expected and could possibly be a source of these contaminants in the river.
Keywords: Organic Pollutants; Water Research Commission; Emerging pollutants contaminants; Umgeni and Msunduzi Rivers